Seeds morphology, anatomy, and quality of Musa balbisiana and Musa acuminata after storage - Mertya Anugrah; Abdul Qadir; Eny Widajati; Sukartini (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2025)
The fluctuations in seed food reserves can trigger a cascade of physiological and biochemical events that ultimately manifest as discernible changes in seed morphology and anatomy.  The purpose of this research was to evaluate seeds morphology, anatomy, and quality of Musa balbisiana “Klutuk NTT” and Musa acuminata “Sumatrana” accessions and their storability. Morphological evaluation included seed size and the weight of 100 grains. Anatomical evaluations were carried out for seed structure. The seed quality of the Klutuk NTT banana accessions was observed after being stored for 5, 25, and 41 months, while the Sumatrana banana accessions were observed after being stored for 5, 23, and 41 months. The Klutuk NTT seeds are sized 4 mm to 5.8 mm, while Sumatrana seeds are sized 4 mm to 5 mm. The Klutuk NTT and Sumatrana seeds had a seed coat, endosperm, embryo, micropyle, inner and outer integuments, chalazal, and operculum. The embryonic structure of both Klutuk NTT and Sumatrana seeds exhibited an inverted T-shape. After storage, the two accessions showed significant differences in moisture content, germination rate, vigor index, and seedling growth performance. The Klutuk NTT accessions demonstrated a significant increase in moisture content, germination rate, vigor index, and seedling emergence uniformity, suggesting improved seed performance after storage. In contrast, the Sumatrana accessions showed a significant decline in all measured parameters, except for moisture content. These results suggest that the Klutuk NTT accession may possess a physiological seed dormancy mechanism. Keywords: Banana; germination; true seed; viability; vigor